Implementation of Enterprise Resource Planning (ERP) as Part of Management Information System - Ahmad Affine Lazuardi; Hendra Kustiono; Radif (Takaza Innovatix Labs Ltd., 2026)
The rapid development of information technology requires business organizations, from Micro, Small, and Medium Enterprises (MSMEs) to large corporations, to adopt integrated digital platforms. Enterprise Resource Planning (ERP) is a core component of modern Management Information Systems (MIS), integrating various operational functions into a single, centralized database. This article examines the implementation of ERP as an integral part of MIS by synthesizing empirical data from 20 previous journal articles. The analysis focuses on optimizing functional management (HR, Finance, Inventory, and Omnichannel Distribution), the real-world impact on financial performance and company value, and the structural and psychological challenges during implementation. The literature synthesis indicates that successful ERP system implementation can improve operational efficiency, data governance transparency, profit reporting accuracy, and accelerate inventory turnover. However, its contribution to increasing market value on the stock exchange is conditional and is strongly influenced by company size and the macroeconomic stability of the industrial sector. Internally, the biggest challenges lie in user discipline in timely data input and resistance to technological adaptation. While psychological factors such as work motivation have not been shown to moderate employee performance effectiveness systematically.